2011
DOI: 10.1371/journal.pmed.1001082
|View full text |Cite
|
Sign up to set email alerts
|

Population Density, Water Supply, and the Risk of Dengue Fever in Vietnam: Cohort Study and Spatial Analysis

Abstract: Results from 75,000 geo-referenced households in Vietnam during two dengue epidemics reveal that human population densities typical of villages are most prone to dengue outbreaks; rural areas may contribute as much to dissemination of dengue fever as do cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
171
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(207 citation statements)
references
References 28 publications
16
171
5
3
Order By: Relevance
“…A recent publication showed that secondary DENV-2 infections could result from more virulent clades than others, depending on the serotype of the primary infecting serotype, DENV-1 or DENV-3. 21 Under these conditions, the development dynamics of epidemics, the function of the implicated genotypes, and the intervals between the successive epidemics, 22 the immune and genetic status of the population, 23 and other environmental factors such as the population density, 24 the climate and density of mosquitoes of the Aedes genus, 25 could create specific situations in each endemic region and thus create many confounding factors. This could explain the differences in results shown in various publications on the theme of clinical presentation by serotype.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication showed that secondary DENV-2 infections could result from more virulent clades than others, depending on the serotype of the primary infecting serotype, DENV-1 or DENV-3. 21 Under these conditions, the development dynamics of epidemics, the function of the implicated genotypes, and the intervals between the successive epidemics, 22 the immune and genetic status of the population, 23 and other environmental factors such as the population density, 24 the climate and density of mosquitoes of the Aedes genus, 25 could create specific situations in each endemic region and thus create many confounding factors. This could explain the differences in results shown in various publications on the theme of clinical presentation by serotype.…”
Section: Discussionmentioning
confidence: 99%
“…The urban areas are comprised of 391 census units in Hermosillo and 69 in Navojoa. Neighborhood characteristics included: median age as an indicator of susceptibility, unemployment status (%) as an indicator of socio-economic standing, population with no health care (%) as a modifier of being detected and reported as a dengue case, migrant population in the last 5 years (%) as an indicator of mobility of the population and potential viral introduction, and houses with no piped water (%) as a proxy for water storage which may provide larval habitat and overall infrastructure that may influence vector-human contact (Padmanabha et al, 2010;Schmidt et al, 2011). Three additional variables; persons per house, occupied houses (%) and population density (persons per hectare) were used as indicators of proximity between individuals which can influence Ae.…”
Section: Data Sources and Variablesmentioning
confidence: 99%
“…Three additional variables; persons per house, occupied houses (%) and population density (persons per hectare) were used as indicators of proximity between individuals which can influence Ae. aegypti dynamics and the transmission patterns among residents (Rodrigues et al, 2015;Schmidt et al, 2011). Census data were available for 2010 which coincided with the outbreak in Hermosillo but was two years after the 2008 outbreak in Navojoa.…”
Section: Data Sources and Variablesmentioning
confidence: 99%
“…Cependant si ces facteurs influencent potentiellement le cycle de contamination, ils ne sont pas systéma-tiquement identifiés comme tels, car le résultat des causalités non linéaires entre ces facteurs dépend des contextes locaux. La connaissance de ces relations permet malgré tout la mise en oeuvre d'actions à différentes échelles pour tenter d'améliorer les conditions de santé publique : contrôle régulier des gîtes en eau (Abe et al, 2005), mesures de protection intra domiciliaires (Singh et al, 2011), amélioration des conditions d'accès à l'eau des populations (Schmidt et al, 2011), interventions selon les types d'usages du sol (Thammapalo et al, 2008) ou encore politiques de planification urbaine (De Mattos Almeida et al, 2007).…”
Section: L'environnementunclassified